COMPARISON OF PRODUCTION PERFORMANCE OF STRIPED CATFISH LARVAE (Pangasianodon hypophthalmus) FED WITH LIVE AND FROZEN DAPHNIA - Otie Dylan Soebhakti Hasan; Adang Kasmawijaya; Azam Bachur Zaidy; Rina Rina (Indonesian Aquaculture Journal, 2022)
Daphnia magna as a live feed in the maintenance of striped catfish larvae in the form of frozen feed is still limited. Evaluation of the production performance of striped catfish larvae using live feed D. magna in both live and frozen compared with feeding Tubifex became the objective of this research activity. The experimental design used feed treatment with Tubifex (P1) as a control, live D. magna (P2), and frozen D. magna (P3) with four experimental replications for 15 days of rearing using a completely randomized design. Twelve aquariums with a water volume of 150 L were used in the experiment. Striped catfish larvae (1.5 cm TL), as many as 9 fish/L were stocked in each aerated aquarium. The amount of feed given was 15% of the weight of fish biomass with a frequency of 4 times a day and increased every day by 10% from the total feed of the first day. Results of the experiment showed different feeding significantly affected absolute length growth, total biomass, and feed conversion, with the best treatment being Tubifex (P1) with values of 0.6 ± 0.02 cm, 83.93 ± 5.99 g, and 1.31, respectively. The best growth rate of weight and length were obtained on larvae fed Tubifex (P1). The best protein efficiency and retention ratio resulted from frozen D. magna feed (P3) treatment of 12.45 and 7.11%, respectively. Live and frozen D. magna was not significantly different, so frozen D. magna feed can be used as an alternative natural feed with a high level of availability.